Saúde mental entre alunos das séries terminais do Ensino Fundamental: percepções e estratégias curriculares - Braga, Émerson dos Santos (2024)
This research examines educators' perception of the mental health of students in the final years of elementary school in a high-standard private school in the capital of São Paulo. The study explores how neoliberal influences permeate the school environment, directly impacting students' psychological well-being. Using the Critical Collaborative Research methodology, the analysis addresses both the institution's pedagogical proposal and the educators' responses to specific questionnaires, capturing the complexity of the interactions between pedagogical practices and students' well-being. The evaluation of this proposal reveals a conflict between the demands of the job market and the aspirations for educational practices that promote social transformation and integral development of the student, configuring the curriculum as a field of dispute between neoliberal imperatives and the ideals of an emancipatory education. The study adopts Bader Sawaia's (2001) concept of ethical-political suffering to describe how mental health issues can be exacerbated by competitive dynamics and family pressure for academic performance. The results of the questionnaires indicate that educators are aware of the negative impacts of these pressures on the psychological well-being of students. Although the term 'neoliberal' was not explicitly used by participants, they recognize that many of the challenges faced by students are amplified by competitive structures and practices that reflect social and familial demands, manifested in the school environment. Despite the lack of familiarity with the "Good Living" philosophy, educators' proposals for curricular and pedagogical improvements reflect the principles of this philosophy, which emphasizes collective well-being, cooperation and harmony with the environment. This indicates a predisposition towards educational approaches that transcend neoliberal norms, suggesting the possibility of aligning school practices with more humanistic and sustainable values. The research proposes that the results obtained can support the implementation of a continuing training program for educators at the institution, aiming to integrate the principles of "Good Living" into the school curriculum. This program, aiming to create a healthier and more inclusive educational environment, would be developed through a collaborative process that involves the active participation of educators in the reflection and reformulation of pedagogical practices. This study contributes significantly to the field of education by highlighting the urgent need for educational practices that promote students' mental health and well-being, challenging neoliberal influences and encouraging a more integrated pedagogical approach focused on "Good Living"